2001
DOI: 10.1074/jbc.m104581200
|View full text |Cite
|
Sign up to set email alerts
|

A Factor of Inducing IgE from a Filarial Parasite Is an Agonist of Human CD40

Abstract: Immune responses to parasitic helminth are usually characterized by quite mysterious phenomena: dominance of Th2-like immunity and antigen-nonspecific IgE secretion. We previously purified a factor from Dirofilaria immitis that induces antigen-nonspecific IgE in rats and named it DiAg. In the presence of IL-4, DiAg induces mouse B cells to secrete IgE, which is antigennonspecific polyclonal antibody. We investigated the biochemical characteristics of DiAg as a factor of inducing IgE in this study. Recombinant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
(33 reference statements)
0
14
0
Order By: Relevance
“…Therefore, it is likely that NO production driven by living worms or their products is associated with parasite survival rather than host protection. We have recently demonstrated that DiAg preferentially induces polyclonal IgE synthesis by B cells (6,19). These findings suggest that DiAgdriven NO production is involved in the down-regulation of parasite-specific responses.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, it is likely that NO production driven by living worms or their products is associated with parasite survival rather than host protection. We have recently demonstrated that DiAg preferentially induces polyclonal IgE synthesis by B cells (6,19). These findings suggest that DiAgdriven NO production is involved in the down-regulation of parasite-specific responses.…”
mentioning
confidence: 94%
“…NPAs are predominantly located in the pseudocoelomic fluid of ascarids (including the porcine intestinal roundworm Ascaris suum) or on the surface of filariae (including the canine heartworm Dirofilaria immitis) and are secreted as a major component of the excretory-secretory (ES) product (7). More recently, we have found that the D. immitis polyprotein (DiAg; a Dirofilaria NPA) can bind to human CD40 molecules and induces antigen-nonspecific polyclonal immunoglobulin E (IgE) production by highly purified human and murine B cells in the presence of interleukin-4 (6,19). To verify that DiAg signaling occurs via CD40, we examined the effect of DiAg on NO synthesis by CD40-bearing and CD40-defective macrophages.…”
mentioning
confidence: 99%
“…These findings indicate that DiAg prevents Th1-type immune responses via an IL-10-dependent mechanism, thereby upregulating Th2-type responses. rDiAg monomer induces nonspecific IgE synthesis in two genetic backgrounds: BALB/c (Th2-dominant strain) and C57BL/6 (Th1-dominant strain) mice (18,33). In addition, diabetes (which is mediated by Th1 cells) in nonobese diabetic mice can be completely prevented by treatment with rDiAg monomer (17), indicating that the parasitic molecule can preferentially trigger a Th2-dominant response independent of the genetic background of hosts.…”
Section: Discussionmentioning
confidence: 91%
“…One of their strategies is the production of molecules that have homologies to host immunoregulatory molecules, such as cytokines (4,7,12,26). We have recently shown that DiAg monomers functionally bind to CD40 (18,34). Since DiAg dimers failed to induce cell expansion, IL-10 production, and IgE synthesis in B cells from CD40-deficient mice (data not shown), CD40 also appears to mediate DiAg dimer signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation